Strategi Penerapan E-Bisnis dalam Optimalisasi Pemasaran Produk Pertanian: Studi Kasus pada UMKM Agribisnis - Ari Susanto (PUTRA JAWA PUBLISHER, 2024)
The development of information technology has brought significant changes in marketing strategies, including in the agribusiness sector. This study aims to analyse the strategy of implementing e-business in optimising the marketing of agricultural products in agribusiness MSMEs. A qualitative approach is used with a case study method on several MSMEs in the agribusiness sector that have adopted digital platforms. The results show that the application of e-business, through the use of social media, marketplaces, and e-commerce websites, is able to increase market reach, marketing efficiency, and competitiveness of agricultural products. However, challenges such as farmers' digital literacy and limited technological infrastructure are still major obstacles. This research suggests increased digital training for MSME players and government support in providing adequate technological infrastructure. With proper implementation, e-business can be a strategic solution to overcome traditional marketing constraints in the agribusiness sector.